CONSERVATION POLICIES AND NON TIMBER FOREST PRODUCTS DEVELOPMENT IN CAMEROON (2012)
Non timber forest products (NTFPs) are forms of biodiversity used for food, medicines and income in Cameroon. Government therefore, seeks better conservation policies and innovative mechanisms to fund NTFPs development. Unfortunately, viable mechanisms are untested in Cameroon, making it difficult to envisage what nature of policy is needed and at what scale. To address this gap, research was conducted to assess willingness to accept a conservation tax at a macro level, and understand the NTFPs potential, access, control and benefits sharing, at a micro level in Cameroon. Quantities of selected NTFPs collected by households in four villages (Abakoum, Djebe, Djenou, Nemeyong) in a Community Forest (CF) in south eastern Cameroon were monitored daily using log books. Baillonella toxisperma and Irvingia gabonensis were monitored for three years and Ricinodendron heudelotii over two. Using questionnaire, information was sourced from 152 household heads (Bantus and Pygmies) nominated by other villagers (based on long-term residency and life-long collection of the NTFPs). Social information was sourced on demography, use and access rights to NTFPs. Participatory mapping corroborated distances to collection points of NTFPs. Furthermore, a random sample of 304 respondents in the city of Yaounde was interviewed using structured questionnaire, to evaluate willingness and conditions for accepting taxation for forest conservation. Data were analyzed using descriptive statistics, Chi-square, correlation and Kendall coefficient of concordance at p = 0.05. More Pygmies than Bantus collect Ricinodendron heudelotii (64.0% and 58.0%). However, both groups collected Irvingia gabonensis and Baillonella toxisperma to the same degree (100.0%). The furthest distance to collection sites was over 10 km in Abakoum and Djebe with higher Pygmy populations. Djebe is second after Abakoum in "off-season" collection of Baillonella toxisperma and Irvingia gabonensis. Positive correlations were observed between mean "off-season" production of Baillonella toxisperma (r = 0.78), Irvingia gabonensis (r = 0.89) and Ricinodendron heudelotii (r = 0.39), and the Pygmy community populations. A total discounted revenue of over $US 39931, 73261, and 149951 was projected to accrue from sales of Baillonella toxisperma, Irvingia gabonensis and Ricinodendron heudelotii respectively, over six years. This is however at variance with the local perceptions of the resources' market value, where it is influenced by a demand mix. Use of NTFPs in forests can therefore, generate $US 10.5 per hectare per year, against an estimated $US1.9 per hectare per year in timber fees. About 78.0% of the city respondents were willing to support biodiversity conservation through taxation, as proxy for sustaining NTFP supply. However, 82.9% were unwilling to reveal amounts they would be willing to pay. Concordance was significant on forest conservation tax being conditional on available, detailed, socially differentiated information on local level benefits sharing, transparency in funds management and freedom of contributors to opt out of the policy process. Potentially, revenue from non-timber forest products can surpass fees from timber per hectare and targeted fiscal policies can generate additional funds for NTFPs development. However, this scenario requires policies based on detailed understanding of local level social and production dynamics to guarantee equity in sharing of benefits.